Co3O4-induced area-selective growth of Ni(OH)2 cellular arrays for high-capacity supercapacitor electrode. (April 2022) - Fan, Jiahui; Chen, Aiying; Xie, Xiaofeng; Gu, Lijian
Highlight: Ni(OH)2 cellular arrays are synthesized by Co3 O4 NSs as assisted agent. Co3 O4 /Ni(OH)2 hybrids are aligned with an open cellular nanostructure. Ultrahigh specific supercapacitance is obtained, exceeding the theoretical value. The asymmetric supercapacitor device exhibits a high energy density. The ultrathin cellular arrays and hybrid structure enhance the supercapacitance. Abstract: Three-dimensional (3D) hybrids are very valuable in the construction of supercapacitor electrodes. Ni(OH)2 cellular arrays were in-situ grown on nickel foam using Co3 O4 nanosheets (NSs) as nucleating agent. The formation, microstructure and supercapacitance performance of the Co3 O4 /Ni(OH)2 cellular arrays are systematically investigated. The Co3 O4 /Ni(OH)2 arrays present an open cellular nanostructure with ultrathin Ni(OH)2 walls. The Co3 O4 /Ni(OH)2 prepared by hydrothermal reaction of 12 h delivers a super-high specific capacitance of 4396 F g −1 at 1 A g −1, above the theoretical capacitances of both the Ni(OH)2 and Co3 O4 . Additionally, the Co3 O4 /Ni(OH)2 electrode shows an excellent cycle performance by retaining 80.1% after 5000 cycles and a stable rate capability by decreasing 21.1% from 1 to 10 A g −1 . The assembled asymmetric supercapacitor reaches a large energy density of 32 Wh kg −1 at 7999 W kg −1 by Co3 O4 /Ni(OH)2 as anode and reduced graphene oxides as cathode. The prominent high-capacity performance can be attributed to the cellular arrays, ultrathin hybrid NSs and synergetic reactions of the Ni(OH)2 and Co3 O4 . The proposed technology is also suitable for producing other multi-component oxide/hydroxide arrays as electroactive materials for energy storage devices. Graphical abstract: Image, graphical abstract